Refugees and asylum seekers living in the Australian Community: the importance of work rights and employment support - Fleay, Caroline; Hartley, Lisa; Kenny, Mary Anne (Australian Council of Social Service, 2013)
While Australian legislation allows for the mandatory detention of asylum seekers arriving without a valid visa, in recent years the Australian Government has released thousands from immigration detention prior to their protection claims being finalised. This article outlines the results of interviews with eleven men who had been released into such community-based arrangements after long periods of immigration detention. The major challenge for most of the men who had been granted the right to work upon their release was securing employment, while being denied the right to work was the major challenge for those released without this right. This article explores the social and personal benefits that employment can offer asylum seekers and refugees and the implications it has for integration into their host country.